The Potentiality of microbial fuel cell anode with enhanced electron transfer - Baranitharan, E. (2014)
Palm oil mill effluent (POME) is an organic waste material produced at the oil palm mills. In its raw form, POME is highly polluting due to its high content of biological (BOD) and chemical oxygen demand (COD). In this context, treatment of wastewater using MFC (Microbial fuel cell) seems to be promising technology because it reduces operation energy requirement and shows efficient treatment too. In the present work, MFC with POME were used to study the effect of different electrode materials and to harvest high power density (PD) using controlled inoculum. Three different electrode materials such as PACF (Polyacrylonitrile carbon felt), SFCC (Single forward carbon cloth) and GR (Graphite rod) were used as anode and cathode materials for the MFC experiments. Among the raw POME and different concentrations of POME used, the PACF, SFCC with raw POME (60600 mg/L) showed the maximum power density (PD) of about 45mW/m2 and 102.50 mW/m2 respectively but both PACF and SFCC showed low coulombic efficiency (CE) of about 0.8 % and 2.2 % respectively as well as low COD removal efficiency of about 45 % and 54.45 % respectively. The PACF and SFCC MFC with 1:50 dilution (964 mg/L) showed higher COD removal efficiency of about 70 % and 78 % respectively and also CE of about 24% and 51% respectively but showed low PD of about 22 mW/rn2 and 28.48 mW/m2respectively. While, GR with raw POME showed very low PD, CE and COD removal efficiency of about 11.238 MW/M2, 0.2% and 28% respectively. Predominant microbes from anaerobic sludge (AS) were successfully isolated and identified as Pseudomonas aeroginousa, Pseudomonas mendocina, Pseudomonas viridiivida, Acetinobacter schindleri, Actinobacillus capsulatus and Brevibacterium paucivoransusing BIOLOG gene III analysis. Biofilm formation on electrode surface was analyzed using Fourier transformed infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA) and field emission scanning electron microscopy (FESEM) analysis. Biofilm was characterized using PCR-DGGE (polymerase chain reaction - denaturing gradient gel electrophoresis) analysis and sequencing and identified the predominant microbes in biofllm which includes Azospiraoryzae, Acetobacterperoxydans and Solimonasvariicoloris.The electrochemical activities have been investigated by electrochemical impedance spectroscopy (EIS). In the final experiment, MFCs inoculated with controlled inoculum (CI) and POME as substrate. The CI was made using the microorganisms which are adapted and grown in palm oil mill effluent. CI was the mixture of fermentative and electrogenic microorganisms. It consists of electrogen (Pseudomonas aeroginousa) from AS and - fermentative microorganisms (Azospiraoryzae, Acetobacterperoxydans, Solimonasvariicoloris) from biofilm since no electrogen found in biofllm. The MFC operated with CI reached the maximum power density of 107.35mW/rn2, which was two times higher as compared to MFC operated with AS as inoculum. The maximum CE of 74 % was achieved from the MFC with CI, which was 50% higher than the CE with AS. But, it showed lower COD removal efficiency of about 32%, which might be due to the absence of required fermentative microorganisms in CI to utilize POME. EIS and the simulated results showed the reduction of charge transfer resistance (Rct) by 19.5% during the operation of the cell with CI. These results demonstrate that the power output of MFCs can be increased using CI.